2005
DOI: 10.1161/01.cir.0000158487.80483.09
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Dimethylarginine Dimethylaminohydrolase Reduces Tissue Asymmetric Dimethylarginine Levels and Enhances Angiogenesis

Abstract: Background-This study was designed to determine whether overexpression of the enzyme dimethylarginine dimethylaminohydrolase (DDAH) could enhance angiogenesis by reducing levels of the endogenous nitric oxide synthase (NOS) inhibitor asymmetric dimethylarginine (ADMA). Methods and Results-In DDAH1 transgenic (TG) and wild-type mice (each nϭ42), the role of DDAH overexpression on angiogenesis was studied by use of the disk angiogenesis system and a murine model of hindlimb ischemia (each nϭ21). After surgery, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 47 publications
2
107
0
Order By: Relevance
“…Furthermore, data by Matsumoto et al (6) are in line with findings in DDAH transgenic mice, which exhibit low ADMA levels as a result of high DDAH I activity (22). These animals are less susceptible to vascular lesions (23), which is in part attributable to enhanced angiogenic potential (24), and they have a higher ability to regenerate endothelium (24). In contrast, knocking out this enzyme compromises ADMA degradation, which eventually results in inhibition of NO synthesis, increased vascular resistance and hypertension (25).…”
Section: The Dawn Of a New Treatment For Ckd?supporting
confidence: 54%
“…Furthermore, data by Matsumoto et al (6) are in line with findings in DDAH transgenic mice, which exhibit low ADMA levels as a result of high DDAH I activity (22). These animals are less susceptible to vascular lesions (23), which is in part attributable to enhanced angiogenic potential (24), and they have a higher ability to regenerate endothelium (24). In contrast, knocking out this enzyme compromises ADMA degradation, which eventually results in inhibition of NO synthesis, increased vascular resistance and hypertension (25).…”
Section: The Dawn Of a New Treatment For Ckd?supporting
confidence: 54%
“…One mechanism occurs through renal excretion of ADMA and the other mechanism is through conversion to citrulline and methyamines by the action of DDAH (42). Indeed, overexpression of human DDAH1 in transgenic mice results in a 2-fold increase in NOS activity and nitric oxide production that is associated with 2-fold reduction in plasma ADMA (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known regarding the role of NO in ESC differentiation to ECs. In the adult mammal, we and others have shown that NO is a potent mitogen and survival factor for ECs, as well as an angiogenic agent [15][16][17]. Because of the important role NO plays in maintaining EC growth in adults, we hypothesized that it may also play a critical role in endothelial development.…”
Section: Introductionmentioning
confidence: 98%